Thoracoscopic esophagectomy with extended lymph node dissection in the left lateral position: technical feasibility and oncologic outcomes. Issue 2 (1st March 2014) - Ninomiya, I.; Osugi, H.; Fujimura, T.; Fushida, S.; Okamoto, K.; Maruzen, S.; Oyama, K.; Kinoshita, J.; Tsukada, T.; Kitagawa, H.; Takamura, H.; Nakagawara, H.; et al.
Summary: The aim of this study was to estimate the technical and oncologic feasibility of video-assisted thoracoscopic radical esophagectomy (VATS ) in the left lateral position. From J anuary 2003 to D ecember 2011, 132 patients with esophageal cancer underwent VATS . The mean duration of the thoracic procedure and the entire procedure was 294 ± 88 and 623 ± 123 minutes, respectively. Mean blood loss during the thoracic procedure and the entire procedure was 313 ± 577 and 657 ± 719 g, respectively. The mean number of dissected thoracic lymph nodes was 32.6 ± 12.9. There were four in-hospital deaths (3.0%); two patients (1.5%) died of acute respiratory distress syndrome and two patients (1.5%) died of tumor progression. Postoperative unilateral or bilateral recurrent laryngeal nerve (RLN ) palsy, or pneumonia was found in 33 (25.0%), 21 (15.9%), and 27(20.5%) patients, respectively. The patients were divided into the first 66 patients who underwent VATS (G roup 1) and the subsequent 66 patients (Group 2). The numbers of cases who underwent neoadjuvant or induction chemotherapy for T 4 tumor and intrathoracic anastomosis were higher in G roup 2 than in G roup 1. The duration of the procedure, amount of blood loss, and the number of dissected thoracic lymph nodes were not different between the two groups. The total number of dissected lymph nodes was higher in G roup 2 than in G roup 1 (72.6 ± 27.8 vs. 62.6 ± 21.6, P = 0.023). The rate of bilateral RLN palsy was less in G roup 2 than in G roup 1 (7.6% vs. 24.2%, P = 0.042). The mean follow-up period was 38.7 months. Primary recurrence consisted of hematogenous, lymphatic, peritoneal dissemination, pleural dissemination, and locoregional in 15 (11.3%), 20 (15.1%), 3 (2.3%), 4 (3.0%), and 5 patients (3.8%), respectively. The rate of regional lymph node recurrence within the dissection field was only 4.5%. The prognosis of patients with lymph node metastasis was significantly poorer than that of patients without lymph node metastasis. However, the prognosis of the 11 cases that had metastasis only around RLNs was similar to that of node-negative cases. Thirteen patients with pathological remnant tumor (R 1 or R 2) did not survive longer than 5 years at present. The overall 5-year survival rate of stage I, II, and III disease after curative VATS was 82.2%, 77.0%, and 52.3%, respectively. Expansion of VATS criteria for patients after induction chemotherapy for T4 tumor or thoracoscopic anastomosis did not adversely affect the surgical results by experience. Although the VATS procedure is accompanied by a certain degree of morbidity including RLN palsy and pulmonary complications, VATS has an excellent locoregional control effect. In addition, the favorable survival after VATS shows that the procedure is oncologically feasible.